Seroprevalance of brucellosis in cattle, sheep and goat in hatay region - Özkan Aslantaş; Nesrin Turan (Eurasian Journal of Veterinary Sciences)
In this study, numbers of 589,440 and 452 serum samples from sheep, goat and cattle collected from different localities of Hatay region was investigated for the presence of antibodies to Brucella. For this purpose, sheep sera were tested with Rose Bengal Plate Test (RBPT), Serum Agglutination Test (SAT) and Complement Fixation Test (CFT) while goat and cattle sera were investigated with RBPT and sera which have been found positive were confirmed by CFT. Of 589 sheep sera, 4.92 % CFT was found positive by CFT. Sero-examination of goat and cattle sera produced positivities of 1,49 % and 2.21 %, respectively.